2021
DOI: 10.1111/jfpe.13948
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed light treatment reduces microorganisms and mycotoxins naturally present in red pepper (Capsicum annuum L.) powder

Abstract: The impact of pulsed light (PL) treatment on naturally occurring microorganisms, mycotoxins, and on physicochemical properties in red pepper powder was investigated. Powder samples were exposed to different PL treatments up to 61 pulses, with fluence ranging from 1.0 to 9.1 J/cm2. The highest fluence applied (9.1 J/cm2, 61 pulses, 20 s) resulted in 2.7, 3.1, and 4.1 log CFU/g reduction of yeasts, molds, and total plate counts (TPC), where initial microbial loads were 4.6, 5.5, and 6.5 log CFU/g, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…(2023) demonstrated that the degradation rates of AFB 1 , AFB 2 , AFG 1 , and AFG 2 in apple juice were respectively 72.09%, 73.65%, 57.06%, and 69.69% after pulsed light treatment with 40 flashes, and the quality of apple juice was not significantly influenced by pulsed light treatment. Pulsed light with 61 flashes (total light flux of 9.1 J/cm 2 ) could degrade 67.2% AFB 1 in red pepper powder, and the total phenols of treated powder significantly increased (Woldemariam et al., 2022). The degradation level of aflatoxins in rice bran and brown rice were significantly different.…”
Section: Degradation Of Aflatoxins By Physical Methodsmentioning
confidence: 99%
“…(2023) demonstrated that the degradation rates of AFB 1 , AFB 2 , AFG 1 , and AFG 2 in apple juice were respectively 72.09%, 73.65%, 57.06%, and 69.69% after pulsed light treatment with 40 flashes, and the quality of apple juice was not significantly influenced by pulsed light treatment. Pulsed light with 61 flashes (total light flux of 9.1 J/cm 2 ) could degrade 67.2% AFB 1 in red pepper powder, and the total phenols of treated powder significantly increased (Woldemariam et al., 2022). The degradation level of aflatoxins in rice bran and brown rice were significantly different.…”
Section: Degradation Of Aflatoxins By Physical Methodsmentioning
confidence: 99%
“…According to Liu et al [91], approximately 500 mycotoxins have been identified, and among these, aflatoxins, ochratoxins, fumonisins, patulin, trichothecenes and zearalenone are the more frequent in agricultural goods and those with more adverse health effects on humans [92][93][94]. Excluding trichothecenes, all abovementioned mycotoxins are carcinogenic [89].…”
Section: Mycotoxins In Prunus Fruits: a Serious Health Riskmentioning
confidence: 99%
“…Fruit Quality and Postharvest: Today's Challenges and Future Perspectives DOI: http://dx.doi.org/10.5772/intechopen.112638 Some technics, most of them using thermal mechanisms, have been developed to reduce mycotoxins from food [87]; however, in general, mycotoxins are stable including at temperatures of thermal operations (80-121°C). More recently, non-thermal techniques (cold plasma, pulsed light, pulsed electric fields, high pressure processing, electron beam irradiation) have being studied [87,93,94,[103][104][105][106][107][108].…”
Section: Mycotoxins In Prunus Fruits: a Serious Health Riskmentioning
confidence: 99%
“…The same treatment parameters were applied to cause the reduction of total aflatoxins by 50.9%, aflatoxin B 1 by 67.2%, and ochratoxin A by 36.9%. Total phenols increased apparently and significantly, while the total color was slightly changed [ 81 ].…”
Section: Single Detoxification Treatments Used In Solid Foods and Feedsmentioning
confidence: 99%
“…The chemical quality did not show significant changes as a result of this combined effect, but a significant change in the color of peanuts occurred [ 129 ]. In previously discussed studies about pulsed light treatments, the reduction rates of AFT, AFB 1 , and AFB 2 were in the range of 39.2 to 90.2% in red pepper powder and rice with different fluence ranges applied [ 81 , 83 ]. Therefore, combining an acid with pulsed light can be considered a beneficial combination, demonstrating higher efficiency in mitigating aflatoxins than each treatment alone.…”
Section: Simultaneous Detoxification Treatments Used In Solid Foods A...mentioning
confidence: 99%